Implementasi Kurikulum Merdeka dalam Pembelajaran IPAS Kelas 6 SD dan Pemanfaatan LKPD - Dzildiyana Dzildiyana; Shela Nabila; Ach. Cholisur Rahman; Yeni Puji Astuti (LPPM Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Bojonegoro, 2025)
Abstract: The Independent Curriculum emphasizes student-centered learning with competency strengthening and meaningful learning. One of the subjects undergoing reform is Natural and Social Sciences (IPAS), which integrates scientific and social aspects contextually. This study aims to describe the implementation of the Independent Curriculum in sixth-grade IPAS learning and the use of Student Worksheets (LKPD) at SDN Bunpenang 1. The research method used was descriptive qualitative, with sixth-grade teachers and students as subjects. Data collection was conducted through interviews, observation, and documentation, while data analysis used the Miles and Huberman model. The results indicate that IPAS learning is implemented by emphasizing practical activities and linking the material to everyday life. LKPD plays a role in increasing student learning engagement and independence, although it still needs development to make it more engaging and easier to understand. Overall, the implementation of the Independent Curriculum has gone quite well, although it still faces some challenges.